Racial/Ethnic Differences in the Association Between Hospitalization and Kidney Transplantation Among Waitlisted End-Stage Renal Disease Patients. Issue 12 (December 2016) - Newman, Kira L.; Fedewa, Stacey A.; Jacobson, Melanie H.; Adams, Andrew B.; Zhang, Rebecca; Pastan, Stephen O.; Patzer, Rachel E.
Abstract : Background: Even after placement on the deceased donor waitlist, there are racial disparities in access to kidney transplant. The association between hospitalization, a proxy for health while waitlisted, and disparities in kidney transplant has not been investigated. Methods: We used United States Renal Data System Medicare-linked data on waitlisted end-stage renal disease patients between 2005 and 2009 with continuous enrollment in Medicare Parts A & B (n = 24 581) to examine the association between annual hospitalization rate and odds of receiving a deceased donor kidney transplant. We used multilevel mixed effects models to estimate adjusted odds ratios, controlling for individual-, transplant center-, and organ procurement organization-level clustering. Results: Blacks and Hispanics were more likely than whites to be hospitalized for circulatory system or endocrine, nutritional, and metabolic diseases ( P < 0.001). After adjustment, compared with individuals not hospitalized, patients who were hospitalized frequently while waitlisted were less likely to be transplanted (>2 vs 0 hospitalizations/year adjusted odds ratios = 0.57; P < 0.001). Though blacks and Hispanics were more likely to be hospitalized than whites ( P < 0.001), adjusting for hospitalization did not change estimated racial/ethnic disparities in kidney transplantation. Conclusions: Individuals hospitalized while waitlisted were less likely to receive a transplant. However, hospitalization does not account for the racial disparity in kidney transplantation after waitlisting. Abstract : Analysis of USRDS and SRTR listings, hospitalization and transplantation data shows that Black and Hispanic patients are more likely to be hospitalized and less likely to be transplanted, controlling for hospitalization rates. Supplemental digital content is available in the text.